Barriers and enablers to implementation of pressure injury prevention in hospitalized adults: a mixed methods systematic review protocol. Issue 10 (14th October 2020) - Lizarondo, Lucylynn; Stern, Cindy; Carrier, Judith; Godfrey, Christina; Rieger, Kendra; Salmond, Susan; Apóstolo, João; Kirkpatrick, Pamela; Loveday, Heather
ABSTRACT: Objective: The objective of the proposed systematic review is to determine the barriers and enablers (or facilitators) to the implementation of pressure injury prevention among adults receiving care in the hospital setting. Introduction: Hospital-acquired pressure injuries are preventable; however, they remain an ongoing safety and quality health care concern in many countries. There are various evidence-based preventative interventions for pressure injuries, but their implementation in clinical practice is limited. An understanding of the different factors that support (enablers or facilitators) and inhibit (barriers) the implementation of these interventions from different perspectives is important, so that targeted strategies can be incorporated into implementation plans. Inclusion criteria: This review will include quantitative, qualitative, and mixed methods studies that investigate barriers and/or enablers in relation to hospital-acquired pressure injury prevention in hospitalized adults. Only English publications will be considered, with no publication date restrictions. Methods: The systematic review will be conducted in accordance with the JBI methodology for mixed methods systematic review. Published studies will be searched in PubMed, CINAHL, Embase, PsycINFO and Scopus. Gray literature will also be considered. Critical appraisal and data extraction will be performed using standardized tools, followed by data transformation. Data synthesis will follow the convergent integrated approach.